AN OVERVIEW OF WRITTEN FEEDBACK FROM TEACHERS’ PERCEPTION AND PRACTICE - Cory Putri Randa; Suharni Suharni; M. Khairi Ikhsan (TELL - US JOURNAL, 2025)
This study analyses the perceptions and practices of teachers in providing written feedback to students in the English Education Study Program at Universitas PGRI Sumatera Barat. This is a qualitative research. Data were collected through semi-structured interviews with two teachers who taught writing courses and analyzed using thematic analysis technique. The results showed that teachers consider written feedback as an important element in learning to write. They use various techniques of giving written feedback such as providing comments, symbols, colors, and direct revision on students' writing. Providing feedback is adjusted to students' ability level, learning style, and students' needs. Thus, time limitation is the main challenge in providing written feedback.